The Role of Startups in Launching New Outputs: Bacira as a Case Study - Aicha, DOUAR (International Journal of Psychosocial Rehabilitation, 2022)
The purpose of the research paper is to shed light on a set of objectives that are considered as intervening variables while carrying out our project that is featured with socio economic impact. Producing shoes with an original design that communicates a world cultural heritage, and showing its impact on people’s imaginaries are only considered prominent variables if they are associated with healthy and environmental traits. What could be the possible constituents of the shoe making that contribute to the wellbeing of people’s health and to the maintenance of a friendly environment? The latter are two dependent traits that add assets to our product; they guarantee its sustainability in the market. Much focus is attributed to renowned international journals that have dealt with scientific studies about orthopedic soles and their different types. Touring pharmacists and getting in touch with experts resulted in acquiring some conception of desirable health details that concern the feet easement.